APPLICATION OF BALLON BLOWING THERAPY TO REDUCE SHORTNESS OF BREATH IN PATIENTS WITH INEFFECTIVE BREATHING PATTERNS - PUTRI, GIVA RESYINTA; ANDRIANI, LINDA; NISA, SETIA (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2024)
Asthma is one of the respiratory diseases that are often found in the community. Asthma symptoms are characterized by coughing, shortness of breath, shortness of breath and wheezing, making it difficult for children to sleep and do activities. The purpose of this study was to develop treatment in nursing children with respiratory system disorders: asthma with balloon blowing therapy. The subjects of the study were asthma patients. The nursing care provided was Balloon Blowing. The results of the nursing evaluation on the diagnosis of ineffective breathing patterns obtained subjective data, namely the client's mother said that her child's shortness of breath had decreased, the cough had decreased, she was sleeping soundly, and the patient said that her phlegmy cough had decreased. Objective: the patient appeared to have less shortness of breath, less phlegmy cough, and was sleeping soundly. Vital signs: blood pressure: 110/85 mmHg, pulse: 96 x / minute, temperature: 36.8 oC, respiratory rate: 24 x / minute, SpO2: 98%. The results of the nursing evaluation on the diagnosis of ineffective breathing patterns obtained subjective data: the client's mother said that her child's shortness of breath had decreased, the cough had decreased, she was sleeping soundly, and the patient said that her phlegmy cough had decreased. Objective: the patient appeared to have less shortness of breath, less phlegmy cough, and was sleeping soundly. Vital signs: blood pressure: 110/85 mmHg, pulse: 96 x/minute, temperature: 36.8 oC, respiratory rate: 24 x/minute, SpO2: 98%.